Strategy to Improve the Class of Ambon Archipelago Fisheries Port into an Ocean Fishery Port using SWOT Analysis - Ruth Phetrosina Soumokil (Industrial Engineering Study Program, Pattimura University, 2021)
An essential factor for the development of fisheries business, especially fishing activities, is the availability of infrastructure for berths or shelter for fishing vessels and landing their catch fish. The infrastructure is in the form of a Fishing Port or Fish Landing Base as a place or base for fishing vessels. This research aimed to examine the condition of Archipelago Fisheries Port (AFP) on the criteria of an Ocean Fishery Port (OFP), and formulated a strategy for developing Ambon AFP in order to increase its class to an Ocean Fishery Port. The method used in this research was descriptive. Data collection techniques carried out by distributing questionnaires, interviews, and secondary data collection. Sampling was done by using purposive sampling as many as 20 key respondents. The analytical tool used was descriptive analysis and SWOT analysis. The results of this study indicate that: Existing operations in Ambon AFP show increasing development from year to year, both in fish landing, fishing boat visits, supply distribution, non-tax state revenue, and the number of fishers and labour. From the Ambon AFP Development Strategy's research results in the context of improving the class of being an Ocean Fishery Port, ten strategies were produced.